A feasibility study of the combined school/public library in the Municipality of San Juan - Santos, Harriet R., II (Institute of Library Science, University of the Philippines Diliman, 2001)
The purpose of this study was to determine the feasibility of starting a combined school/public library in the municipality of San Juan. Specifically, the study aimed to answer the following questions: What are the reading needs of the constituents of the San Juan Municipality? Do they want/need a library? Is it feasible to establish a combined school/public library in San Juan? What would be the collection, staffing and services to be put up in the combined school/public library of San Juan? A questionnaire and an interview were utilized for this study.